Determinants of Dengue Hemorrhagic Fever Incidents in Medan District, Johor in 2023 - Hutahaean, Sri Hartati Rahayu Lambok; Nababan, Donal; Sinaga, Janno; Manurung, Kesaktian; Sinaga, Taruli Rohana (Open Access Health Scientific Journal, 2025)
Background: Dengue hemorrhagic fever (DHF) is a disease transmitted through the bite of the Aedes aegypti mosquito. Indonesia, as a tropical country with high humidity and a dense population, is particularly vulnerable to the spread of dengue fever. Several risk factors, such as the level of knowledge, societal attitudes, customs related to hanging clothes, and the implementation of the 3M Plus programme, also play a role in the incidence of dengue cases. The Medan Johor District is one of the areas with the highest number of dengue fever cases in Medan City.Method: This study employed an observational analytic design with a cross-sectional approach, conducted in Kuala Bekala Village, Medan Johor District, in 2023. Data were collected through a structured questionnaire designed to measure knowledge, attitudes, preventive behaviours (3M Plus), use of mosquito repellent, and habits related to hanging clothes. The larval index was obtained through direct inspection of the respondents' homes. Data analysis was performed using chi-square tests and logistic regression.Results: There is a significant connection between the incidence of dengue fever and various factors, including the level of knowledge, attitudes, implementation of the 3M Plus programme, use of mosquito repellent, habits related to hanging clothes, and the number of free larvae (p < 0.05). Respondents with a lack of knowledge and at-risk behaviours were significantly more likely to be affected by dengue fever. The habit of hanging clothes poses nearly five times the risk of dengue fever incidence.Conclusion: The incidence of dengue fever in the Medan Johor District is influenced by several modifiable factors related to behaviour and the environment. Health promotion efforts that focus on improving knowledge and the consistent application of the 3M Plus programme are essential. The findings of this research are important for developing dengue fever prevention strategies in high-risk urban areas.